804 The Association Between Hyperoxia after TBI and Degree of Disability in Pediatric Patients. (April 2023) - Tang, Si Jie; Mor, Sirjan; Fine, Jeffrey; Shahlaie, Kiarash
Abstract : INTRODUCTION: Traumatic brain injury (TBI) is a leading cause of death and disability in children worldwide. Hyperoxia has been suggested as a mechanism of secondary injury following adult TBI, but its effect on pediatric patients has not been well-described. METHODS: We conducted a review of all pediatric (≤18yo) TBI patients in a prospective institutional registry from October 2008 to January 2021. PaO2 was extracted from the arterial blood gas report for the first 24 hours after admission to the ICU. The first PaO2, highest PaO2 and the AUC calculation of PaO2 were collected and calculated for each patient. Outcomes 6 months after injury were measured using the modified Rankin Scale (mRS) and dichotomized as favorable (1-2) or unfavorable (3-6). A multivariable logistic regression model was used to determine if minimum PaO2, maximum PaO2, or AUC PaO2, predicted an unfavorable outcome. RESULTS: We identified 122 pediatric patients with severe TBI (GCS 3 – 8) during the study period. The incidence of hyperoxia (PaO2 >300 mmHg) was 25%. Elevated PaO2 values, determined by both maximum and AUC PaO2 within the first 24 hours of hospitalization, was an independent predictor of worse neurological outcome at 6 months. CONCLUSIONS: Using an institutional database, hyperoxia was an independent predictor of poor neurological outcome in pediatric patients. Further studies are needed to determine if efforts to prevent and/or correct hyperoxia are associated with improved outcomes.